Promotion how retailers use special events to improve market share - Clements, Steve; Diamond, Jay.; Diamond Ellen; Diamond Educational Productions (United States : Diamond Educational Productions)
Using Dayton Hudson's parade as an example this video shows how retailers lure customers into their stores though special events.
Keywords: Sales promotion; Marketing; Advertising